2015
DOI: 10.1093/ecco-jcc/jjv179
|View full text |Cite
|
Sign up to set email alerts
|

Fc Receptor-mediated Effector Function Contributes to the Therapeutic Response of Anti-TNF Monoclonal Antibodies in a Mouse Model of Inflammatory Bowel Disease

Abstract: These data support the concept that the mechanism of action for TNF-neutralising drugs may differ across immune-mediated diseases and, potentially, between therapeutics within a particular disease. Our data suggest a specific role of Fc-mediated immune regulation in the resolution of intestinal inflammation by anti-TNF monoclonal antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…The anti-IL-10Rα diminished the therapeutic efficacy of anti-TNF, indicated by the absence of a significant improvement of the endoscopy score (figure 2A,B), the histology score (figure 2C,D) and colon density (figure 2E). Interestingly, it did not affect the effect of the anti-TNF on body weight loss (figure 2F), indicating that body weight loss is dependent on the well-established cachectic effects of circulating TNF, which we have seen before,15 that are less dependent on IL-10. There was an increase in intestinal Il10 expression on treatment with anti-TNF, especially when Il10 levels were expressed relative to levels of key proinflammatory cytokines, such as Ifng or Il1b (figure 2G).…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…The anti-IL-10Rα diminished the therapeutic efficacy of anti-TNF, indicated by the absence of a significant improvement of the endoscopy score (figure 2A,B), the histology score (figure 2C,D) and colon density (figure 2E). Interestingly, it did not affect the effect of the anti-TNF on body weight loss (figure 2F), indicating that body weight loss is dependent on the well-established cachectic effects of circulating TNF, which we have seen before,15 that are less dependent on IL-10. There was an increase in intestinal Il10 expression on treatment with anti-TNF, especially when Il10 levels were expressed relative to levels of key proinflammatory cytokines, such as Ifng or Il1b (figure 2G).…”
Section: Resultsmentioning
confidence: 55%
“…We have previously shown that full monoclonal antibodies (mAbs) against TNF engage Fcγ receptors (FcγRs) and that this Fc–FcγR interaction is necessary for the therapeutic efficacy of anti-TNF in a preclinical model of IBD. Mice without activating FcγRs completely lost response to anti-TNF therapy in the T-cell transfer colitis model, and conversely, a hypofucosylated anti-TNF antibody with increased Fc-binding affinity showed improved efficacy 15 16. Additionally, we have shown that anti-TNF skews human monocytes towards CD206+ regulatory macrophages in an Fc-dependent manner in vitro17 and in vivo,16 and that the response to anti-TNF therapy in both mice and humans was accompanied by the formation of these CD206+ regulatory macrophages in the intestine 16 18.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The commonly used dose of anti-TNF in murine models ranges around 100–300 µg/mouse twice weekly. This dose results in near complete disease remission after 4 weeks of treatment, 14 negating the possibility of testing drugs that potentiate the effect of anti-TNF. We therefore first titrated the anti-mouse TNF to identify a dose that could be considered suboptimal.…”
Section: Resultsmentioning
confidence: 99%
“…37 It may also partly explain why an anti-TNF immunoglobulin (Ig) G1 construct with reduced Fc binding did not ameliorate murine colitis. 38 For biosimilars, data on this possible anti-TNF mechanism of action in IBD are relatively scant, although comparable induction of regulatory macrophages and wound healing in an intestinal cell model was observed for CT-P13 and infliximab RP ( Table 2).…”
Section: Comparing Mechanisms Of Action Across Indicationsmentioning
confidence: 99%